Cities at risk? Exploring the synergies between smartphones and everyday vulnerabilities - Amankwaa, E.F.; Blay, K.B. (Cities, 2019)
Smartphones present new forms of spatiality and sociality for cities worldwide. The sudden outburst in smartphone technologies has revolutionised human relations creating new possibilities of encounter and connectivity. This paper examines people's smartphone usage patterns and highlights how this is increasing human vulnerabilities in cities with resultant wider societal implications. Drawing on the theory of vulnerability, Hofstede's cultural dimension theory and carrying out semi-structured interviews in the United Kingdom and Ghana, the paper reveals that the current scale of usage and addiction to smartphones and social media are fostering emerging forms of everyday vulnerabilities. Victimisation, privacy breach, home emergencies and road accidents are prevalent vulnerabilities in both Accra and London. By comparing participants' smartphone usage patterns and their motives for adopting or ignoring certain social media practices, the study illustrates how the concept of attitudinal vulnerability extends our understanding of Hofstede's theory of collectivism and individualism. While the finding from Accra complicates Hofstede's collectivism label as there seems to be a loss of genuine sense of care and people-centeredness among participants it confirms individualism tendencies among the participants in London though some tendencies of ‘virtual collectivism’ were observed. In conclusion, the study emphasises how significant behavioural changes among smartphone users can reduce human-induced vulnerabilities in cities. By so doing, we add weight to the literature that focuses on the importance of developing context-specific cutting-edge ICT policies vis-à-vis building smart, safe and sustainable cities.
Keywords: Smartphones; Social media networks; Vulnerabilities; Individualism; Collectivism; Smart city